Kimura disease: a case report and review of the literature - Hashim, Hasnur Zaman; Hoo, Fan Kee; Mohd Sazlly Lim, Sazlyna; Mohamed, Mohd Hazmi; Ramachandran, Vasudevan; Ching, Siew Mooi; Wan Sulaiman, Wan Aliaa (Elsevier, 2017)
Introduction: Kimura disease (KD) is a benign chronic inflammatory disorder attributed to an immune mediated hypersensitivity. KD is commonly presented with unilateral subcutaneous tissue swelling in the head and neck area. The course is usually benign except for the potential cosmetic disfigurement. There is no consensus for the treatment of recurrent disease. Aim: To illustrate a case of an uncommon cause of head and neck swelling. Case study: A 41-year-old male presented with a recurrent painless swelling at his of right lower cheek swelling for 6-months. Head and neck examination revealed a 7 × 7 cm firm, non tender mass over the right mandibular region. Other systemic examination was unremarkable. Magnetic resonance imaging of the mass showed a well defined lesion 6 × 3 × 5 cm in size anterior to the right body of mandible. Surgical excision of the mass was done and histopathological examination of the specimen showed fibrocollagenous and fibrofatty tissue infiltrated by chronic inflammatory cells in the pattern of perivascular lymphoid aggregates. The infiltrate is composed predominantly of small lymphocytes and eosinophils. Results and discussion: Here we described a rare cause of painless subcutaneous head and neck swelling that occurred in a middle-aged Asian man. KD usually presents as a painless subcutaneous soft-tissue swellings and associated with regional lymphadenopathy in the head and neck region. Diagnosis of KD is always a clinical dilemma with no specific diagnostic guideline. Though there is no consensus for the treatment of recurrent disease, the overall outcome is good as there is no association with malignancy. Conclusions: KD should be considered in the differential diagnosis of a recurrent head and neck mass.